2019
DOI: 10.3390/toxins11120725
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Combined Hydrogen Peroxide-MlrA Treatment on the Phytoplankton Community and Microcystin Concentrations in a Mesocosm Experiment in Lake Ludoš

Abstract: Harmful cyanobacteria and their toxic metabolites constitute a big challenge for the production of safe drinking water. Microcystins (MC), chemically stable hepatotoxic heptapeptides, have often been involved in cyanobacterial poisoning incidents. A desirable solution for cyanobacterial management in lakes and ponds would eliminate both excess cyanobacteria and the MC that they potentially produce and release upon lysis. Hydrogen peroxide (H 2 O 2 ) has recently been advocated as an efficient means of lysing c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 30 publications
(51 reference statements)
1
14
0
Order By: Relevance
“…This is consistent with the lake treatment of Matthijs et al [27], where MC disappeared in 1-2 days after H 2 O 2 addition. In addition, H 2 O 2 treatments supplemented with the MC-degrading enzyme Mlr-A can further enhance the degradation of MC released by lysing cyanobacteria [97]. Whether interactions between H 2 O 2 and high light intensities affect this microbial degradation of MC is an interesting open question that may deserve further attention in future studies.…”
Section: Microcystin Dynamicsmentioning
confidence: 99%
“…This is consistent with the lake treatment of Matthijs et al [27], where MC disappeared in 1-2 days after H 2 O 2 addition. In addition, H 2 O 2 treatments supplemented with the MC-degrading enzyme Mlr-A can further enhance the degradation of MC released by lysing cyanobacteria [97]. Whether interactions between H 2 O 2 and high light intensities affect this microbial degradation of MC is an interesting open question that may deserve further attention in future studies.…”
Section: Microcystin Dynamicsmentioning
confidence: 99%
“…Results showed that the treatment decreased the abundance of the dominant cyanobacterial taxa and reduction of the intracellular concentration of MC by H 2 O 2 , but the reduction of the extracellular MC was not accomplished in combination with MlrA. Since H 2 O 2 was found to induce the expression of mcyB and mcyE genes involved in MC biosynthesis, the use of H 2 O 2 as a safe cyanobacteriocide still requires further investigation [101]. Several other authors have also suggested measures for water-quality improvement of this lake, including the identification of source water with lower nutrient content for maintaining the volume of the lake, sediment removal [102,103], and sediment phytoremediation [104].…”
Section: A Potential Resolution?mentioning
confidence: 99%
“…The mlr gene cluster is acknowledged as MC-degrading gene, comprising mlrA, mlrB, mlrC, and mlrD, which can express Mlr enzymes to sequentially degrade MC-LR, linearized MC-LR, and tetrapeptide [56,57]. Among them, mlrA is regarded as the most important one, which encode metalloprotease MlrA [58]. Bourne et al first found that microcystinase MlrA can hydrolyze cyclic MC-LR to linearized MC-LR through breaking the peptide bond at Arg-Adda [56,57].…”
Section: Discussionmentioning
confidence: 99%